STRATEGI PEMBANGUNAN KAWASAN TEKNOPOLITAN MELALUI HILIRISASI KELAPA SAWIT DI KABUPATEN PELALAWAN - Yanda Dwitya Nugraha; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the development Strategy the technopolitan area through the downstreaming of palm oil and what are the factors that influence the development of the technopolitan area through the downstreaming of palm oil in Pelalawan Regency. The research method used in this study is a qualitative descriptive research method. Data collection techniques were carried out by means of interviews, observations, and documentation studies. Data analysis was carried out in various steps, namely: data collection, reducing the data that had been collected, describing the data systematically in the form of descriptions and drawing conclusions. Based on the results of the research, the development of the downstream industry still needs attention because the downstream industry is less attractive and the margins are relatively low, but with the STTP, it has been able to produce processed products of crude palm oil such as margarine, cooking oil, soap and cosmetic equipment.Key word: Technopolitan Development Strategy, Pelalawan College of Technology, Crude Palm Oil, Downstream Industries